Lower limb loading during knee up in step aerobics: a pilot study - Błażkiewicz Michalina; Wiszomirska Ida; Kaczmarczyk Katarzyna; Brzuszkiewicz-Kuźmicka Grażyna; Wit Andrzej (Sciendo, 2016)
Study aim: Step aerobics is a form of aerobic power distinguished from other types of aerobic exercise by its use of an elevated platform. The purpose of this study was to examine how the aerobic exercise "knee up" affects kinematic and kinetic parameters and, above all, the length of the muscle contractions.